Socioeconomic status and child psychopathology in the United States: A meta-analysis of population-based studies. (February 2021) - Peverill, Matthew; Dirks, Melanie A.; Narvaja, Tomás; Herts, Kate L.; Comer, Jonathan S.; McLaughlin, Katie A.
Abstract: Children raised in families with low socioeconomic status (SES) are more likely to exhibit symptoms of psychopathology. However, the strength of this association, the specific indices of SES most strongly associated with childhood psychopathology, and factors moderating the association are strikingly inconsistent across studies. We conducted a meta-analysis of 120 estimates of the association between family SES and child psychopathology in 13 population-representative cohorts of children studied in the US since 1980. Among 26, 715 participants aged 3–19 years, we observed small to moderate associations of low family income ( g = 0.19), low Hollingshead index ( g = 0.21), low subjective SES ( g = 0.24), low parental education ( g = 0.25), poverty status ( g = 0.25), and receipt of public assistance ( g = 0.32) with higher levels of childhood psychopathology. Moderator testing revealed that receipt of public assistance showed an especially strong association with psychopathology and that SES was more strongly related to externalizing than internalizing psychopathology. Dispersion in our final, random effects, model suggested that the relation between SES and child psychopathology is likely to vary in different populations of children and in different communities. These findings highlight the need for additional research on the mechanisms of SES-related psychopathology risk in children in order to identify targets for potential intervention. Highlights: In a meta-analysis, youth with lower socioeconomic status had greater psychopathology. This effect was small and consistent for many indices of socioeconomic status (SES). Youth with indicators of serious financial hardship had the most psychopathology. SES was more strongly related to behavior problems than depression or anxiety.